Intra-puparial development of the Cochliomyia macellaria and Lucilia cuprina (Diptera, Calliphoridae) - Barros-Cordeiro, Karine Brenda (2016)
The intra-puparial development of the blowflies Cochliomyia macellaria (n = 310) and Lucilia cuprina (n = 470), was studied under controlled conditions in laboratory. The 3rd instar larvae were reared until they stopped feeding, and the pre-pupae were separated according to the size in larval length and degree of pigmentation and of the cuticle. We observe a set of five continuous events or phases: (1) pupariation, (2) larva-pupa apolysis, (3) cryptocephalic pupa, (4) phanerocephalic pupa and (5) pharate adult. The total time of the intra-puparial development, larva-pupa apolysis to pharate adult, lasted for 120 h (5 days) to C. macellaria and 210 h (8.75 days) to L. cuprina.